Civil Service Education Management (A Study At IPDN North Sulawesi Campus) - Pabisa, Djonny; J.A.M. Rawis; H.N. Tambingon; J.S.J. Lengkong (CV. Inara, 2021)
This research was carried out on the management aspect at the Institute of Governance of Home Affairs (IPDN) North Sulawesi Campus which includes planning, supervising the implementation of management activities, and evaluating the implementation of management activities. This research method uses a qualitative descriptive approach, with data collection through observation, interviews and documentation techniques. The sources of data in this study were IPDN officials, civil servants, and civil servants. The results of this study indicate: 1) Planning for parenting activities at the IPDN, North Sulawesi Campus in Minahasa refers to 3 (three) main components, namely annual activity planning, academic calendar, and civil service life cycle activities. 2) The implementation of caregiving activities is the responsibility of the caretaker ranks by referring to the academic calendar and list of activities in the civil service life cycle. 3) Supervision of the implementation of parenting activities at IPDN North Sulawesi Campus based on a list of life cycle activities is still not optimal based on the findings that lecture and training activities do not appear to be supervised by caregivers. 4) Evaluation of caregiver activities at the IPDN, North Sulawesi Campus in Minahasa is carried out in a normative and sustainable manner through management evaluations at the planning and implementation stages as well as evaluations related to the value of parenting for civil servants who are the duties and responsibilities of home care caregivers.